Effects of substrate, ceramic thickness, translucency, and cement shade on the color of CAD/CAM lithium‐disilicate crowns - Alexandra Czigola; Emese Ábrám; Zoltán Imre Kovács; Krisztina Márton; Péter Hermann; Judit Borbély (2019)
The aim of this in vitro study was to evaluate the effects of substrate colors, different levels of ceramic thickness and translucency, and cement shades on the color difference from a reference color of lithium-disilicate crowns.A premolar tooth preparation was made on a study model for 1.0 and 1.5 mm thick full-ceramic crowns. Digital impressions were taken (3Shape TRIOS) and crowns designed in a CAD program (DentalDesigner). Shade A1 crowns were milled (Everest, Kavo) from high-translucency (HT) and low-translucency IPS e.max (Ivoclar Vivadent) blocks. Twelve substrates were made of different colors and materials (Natural Die Material, Co-Cr, zirconia, and gold-colored alloy). Three different shades of try-in pastes were used to simulate the effect of cements (Variolink Esthetic try-in paste; Ivoclar). Shade measurement was done three times for each crown by a spectrophotometer (VITA Easyshade Advance); averages were compared to a reference crown (A1, HT, 1.5 mm, ND2 abutment, neutral try-in paste) with ΔE00 (CIEDE2000, according to the CIE latest standard) calculated.All the examined parameters influenced the ΔE00 of the crowns. The weakest effect was exerted by the try-in paste.All examined parameters influenced the final color of e.max CAD lithium-disilicate ceramic crowns.Matching the shade of ceramic crowns to the natural tooth color is a great challenge in dentistry. To meet patients' increasing esthetical expectations, CAD/CAM methods are very popular for full-ceramic crowns. However, several factors such as the shade of the abutment, luting cement color, ceramic thickness, and translucency may influence the final color. Our objective was to measure the optical effect of these factors on the final shade of CAD/CAM lithium-disilicate ceramic crowns.